Ultrasonic analysis and lock-in thermography for debonding evaluation of composite adhesive joints. (March 2016) - Palumbo, D.; Tamborrino, R.; Galietti, U.; Aversa, P.; Tatì, A.; Luprano, V.A.M.
Abstract: Glass-fiber reinforced thermosetting plastic adhesive joints were characterized through ultrasonic imaging and lock-in thermographic analysis for assessing the adhesion quality before being subjected to static tensile mechanical tests and to accelerated aging cycles. The mapping of each sample has been obtained. Visual testing were performed on all specimens after the mechanical tests in order to obtain a comparison with ultrasonic and lock-in thermography technique. A quantitative analysis has been carried out to evaluate the ability of lock-in thermography in investigating inadequate bonding and obtaining the validation of the technique by the consistency of the results with the well-established ultrasonic testing. Highlights: The UT C-scan imaging suitable for estimation of the adhesion in GFRP joints. Investigation of defects in adhesively composite joints by lock-in thermography. Quantitatively validation of lock-in thermography for debonding detection.